Immunogenicity correlation in cynomolgus monkeys between Luminex‐based total IgG immunoassay and pseudovirion‐based neutralization assay for a 14‐valent recombinant human papillomavirus vaccine. Issue 8 (21st April 2022) - Bei, Lei; Zhang, Xiao; Meng, Dan; Gao, Shuman; Jia, Jilei; Zhao, Dandan; Luo, Chunxia; Li, Xuefeng; Qiu, Hongbin; Xie, Liangzhi
Abstract: A new virus‐like particle based vaccine covering 14 types of high‐risk and disease‐inducing human papillomavirus (HPV) can offer better coverage against HPV‐induced diseases, particularly cervical cancers. However, the assessment of immunogenicity of the vaccine is an important task, representing not only its significant clinical characteristics, but also a major challenge, in terms of both the suitability of methods and the clinical sample testing throughput supporting clinical development. This work covers the development and evaluation of a method based on Luminex technology (a coded‐bead and flow‐cytometric approach) to assess the HPV‐type specific total immunoglobulin G (IgG). This method can evaluate the antibodies in sera post immunization against multiple types of HPV simultaneously (i.e., with multiplexing capability), save time and cost, and improve test throughput with higher sensitivity and precision than the classical, plate‐based enzyme‐linked immunoassay and competitive Luminex‐based immunoassays. Using cynomolgus monkeys as model, we demonstrated the good correlation between the results from the pseudovirion‐based neutralization assay (PBNA), and the Luminex‐based total IgG assay, supporting that the latter method can be considered as a viable, dependable replacement method for the PBNA supporting immunogenicity evaluation of HPV vaccine in preclinical development and clinical investigation.